The Nigerian Criminal Justice and the Belligerence of Blasphemy: Societal, Judicial and Islamic Law Perspectives - Saliu Jimoh; Abdulwahab D. Shittu; Sodiq S. Mustapha (Jurnal Hukum Novelty, 2022)
Introduction to the Problem: Blasphemy in religion undoubtedly jeopardises the universal human right of freedom of religion in any society. Considering that it is ethno-religiously linked and sensitive in multi-religious environments, the offence is proscribed under the Nigerian laws. With the re-emergence of democracy in Nigeria, the Criminal Justice System became expanded with the birth of a fully-fledged Shariah practice in some areas in Nigeria. The recent death sentence passed on a musician, Aminu, for the alleged offence of blasphemy by a Shariah Court in Kano State attracted the attention of the masses, particularly prompting the question of the propriety or otherwise of the punishment.Purpose/Objective Study: This work examined the societal, judicial and Islamic law perspectives on blasphemy with a view to proffering viable options as punishment for the offence.Design/Methodology/Approach: Doctrinal legal research methodology was adopted, and it involves primary sourcing materials from Quran, Sunnah, Acts and Cases. Secondary sources include journal articles, textbooks, official documents online and in newspaper.Findings:  The findings revealed that the death penalty for the offence is incompatible with the most convincing opinion of scholars, the reality of Nigeria and the international best practices. It is consequently suggested that offence and punishments for blasphemy should be treated as a ta’zir, and the punishment should be less than death.Paper Type: Research Article